ANALYSIS OF THE CALCULATION IMPLEMENTATION OF ARTICLE 22 INCOME TAX COLLECTION ON THE PROCUREMENT OF GOODS AT PT USFATINDO BY THE EXPENDITURE TREASURER - YENI ELFIZA ABBAS (Maqdis: Jurnal Kajian Ekonomi Islam, 2022)
The purpose of the research is to analyze the calculation and collection of Income Tax on the purchase of goods made by the Expenditure Treasurer of PT Usfatindo, whether it was in accordance with the Regulation of the Minister of Finance No. 107/PMK.010/2015 regarding Fourth Amendment To Ministerial Regulation of Finance Number 154/ Pmk.03/ 2010 regarding Collection of Article 22 Income Tax In Regard to The Payment For The Delivery of Goods And The Activities of Import or Other Business Activities. The method used in this research is the descriptive analysis method or case analysis.. Research results indicates that the calculation, collection, and deposit of PPh 22 based on the Regulation of the Minister of Finance Number 107/PMK.010/2015 on Goods Expenditure at PT USFATINDO has been carried out in accordance with the provisions, but in every process of taxation activities of an agency sometimes there are still shortcomings. Therefore, the role of the government including the Directorate General of Tax is needed to continue to guide and remind the importance of taxation in the development of the State in terms of State financing.